EFFECTS OF SELECTED LEAN MANAGEMENT PRACTICES ON FINANCIAL PERFORMANCE OF PRIVATE HOSPITALS IN MOMBASA COUNTY, KENYA - Mohamed, Abdalla Fahad; Mwanyota, Mr. Job (International Journal of Supply Chain Management, 2018)
Purpose: Lean management concept is geared towards waste elimination, eliminating time wasting, money or effort. This is achieved thorough identifying every step the process of a business and cutting out the steps that fail to bring about value. The lean thinking has its origin in engineering although it has been applied to other sectors such as healthcare. The main objective of the study was to examine the effect of lean management practices on financial performance. Methodology: The study adapted a descriptive design with the use of cross-sectional data. The target population was 40 private hospitals in Mombasa County and since the population was small, a census survey was carried out on all the private hospitals in Mombasa County. A questionnaire was used to collect primary data. Out of the 40 research instruments distributed, 37 questionnaires were received and analysed representing 92.5% response rate which was considered adequate. Data analysis was done with the use of SPSS which produced both descriptive and inferential statistics. Results: The findings revealed that all the lean management practices had a significant relationship with financial performance (p<0.05). When individual lean practices were considered, Performance Measurement Systems had a strong positive correlation with financial performance while Total Productive Maintenance had a weak positive correlation with financial performance. Moreover, lean management practices have been employed to a moderate extent and lean management practices affects financial performance to a large degree. Unique Contribution to Theory, Practice and Policy: The study recommended that the private hospitals should concentrate on all aspects of lean management and not one or two since all practices worked in tandem to bring about superior performance.